Evaluation of structural performance between active and passive preloading systems in circular concrete-filled steel tubes (CFST). (1st September 2019) - Milan, Caio C.; Albareda-Valls, Albert; Carreras, Jordi Maristany
Highlights: Preload can increase load capacity in CFST column section. Preloading a CFST section will modify its characteristics for stiffness and ductility. Manipulating the beginning of the confinement effect modifies the CFST's behavior. Abstract: Concrete-filled steel tubes (CFST) are increasingly used thanks to the improved structural performance, especially under compression. This is basically due to the confinement effect provided by the tube, which usually enhances ductility and strength of concrete infill. Several researchers have been focused these last decades on these sections under different assumptions, especially those issues which derive from the construction process; the fact of loading the tube before concreting in preliminary constructive stages leads to a preloading stress which implies a different response of the section than the expected. These issues must be considered in the design process and derive into undesired preloading effects on one of the two components derived from the process itself. Nevertheless, few studies treat the fact of preloading as a design method itself before being under service loads (active methods) to enhance the capacities of CFST sections. This paper analyses and compares 4 different methodologies (2 passive versus to 2 active preloading methods) by describing the potential benefits and consequences of them on the whole section; while sometimes a pre-stress ratio on one component may enhance the global mechanical response, sometimes it does not and becomes even harmful. The ratio of confinement effect over the core and especially when it becomes activated reveals the grade of real enhancement of the compressive response of the section in terms of ductility and strength.